Микстура от косоглазия: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2003)
Экземпляры: ф.15 (ретро) / Инвентарный номер: 38590 / Цена: / Сис.шифр: 84Р6 / Авт.знак: Д 67 / ББК: 84(2Рос = Рус)6